A Comparison of Nursing Education and Workforce Planning Initiatives in the United States and England. (November 2017) - White, Elizabeth
Health care systems in England and the United States are under similar pressures to provide higher quality, more efficient care in the face of aging populations, increasing care complexity, and rising costs. In 2010 and 2011, major strategic reports were published in the two countries with recommendations for how to strengthen their respective nursing workforces to address these challenges. In England, it was the 2010 report of the Prime Minister's Commission on the Future of Nursing and Midwifery, Front Line Care: The Future of Nursing and Midwifery in England . In the United States, it was the Institute of Medicine's report The Future of Nursing: Leading Change, Advancing Health . The authors of both reports recommended shifting entry level nursing education to the baccalaureate degree and building capacity within their educational systems to prepare nurses as leaders, educators, and researchers. This article will explore how, with contrasting degrees of success, the nursing education systems in the United States and England have responded to these recommendations and examine how different regulatory and funding structures have hindered or enabled these efforts.